Analisis Pengaruh Informasi Arus Kas Terhadap Peningkatan Laba (Studi Kasus Pada Perusahaan Manufaktur Di Bursa Efek Indonesia) - Armuni Jokta Mesu; Iing Lukman; Eka Sariningsih (Universitas Malahayati, 2013)
Consolidated cash flow is a useful reports for managers, investors, creditors and other userswhere the report can give a company's cash flows in accordance with the classification of activities.Consolidated cash flow needs to be analyzed to assess the ability of companies to generate cash so thattrust creditors, investors and other business partners can still be maintained by the company.Companies with excess cash flow will have better performance than other firms because they can takeadvantage of various opportunities that may not be acquired by other companies. The objective ofresearch in writing this essay is to determine whether there is influence between cash flow informationthat consists of operating cash flow, cash flow investing and financing cash flow to increase in profitsaround the date of publication of financial statements. Samples were manufacturing companies with atotal sample of 34 companies. The analytical tool used was multiple linear regression analysis .Theresults of this study showed that based on hypothesis testing simultaneously Fcount = 65.213> Ftable(2.92) and the p-value (0.000) <α (0.005) we can conclude that the Ha was accepted that the cash flowinformation composed of operating cash flow (X1), cash flow investment (X2) and cash flow financing(X3) significantly influences the increase in profits. Testing for the hypothesis was partially using the ttest, thus partially that the operating cash flow and financing cash flow significantly influences theincrease in profits because tcount > from ttable and the p-value was (<0.05). While the investment cashflow did not significantly affect the increase in profits because tcount < from ttable and the p-value (>0.05).Keywords: Cash Flow Information, Earnings